Visceral Leishmaniasis: A Differential Diagnosis to Remember after Bone Marrow Transplantation - Margarida Dantas Brito; Fernando Campilho; Rosa Branca; Carlos Pinho Vaz; Cristina Silva; Teresa Sousa; Carlos Mendes; António Campos (Case Reports in Hematology)
Leishmania infection in immunocompromised hosts is reported in the literature, mostly concerning human immunodeficiency virus infected patients. It is not well characterized in the context of stem cell transplantation. We report a rare case clinical case of visceral leishmaniasis after allogeneic bone marrow transplantation. A 50-year-old Caucasian male was referred to allogeneic bone marrow transplantation with a high-risk acute lymphoblastic B leukemia in first complete remission. Allogeneic SCT was performed with peripheral blood stem cells from an unrelated Portuguese matched donor. In the following months, patient developed mild fluctuating cytopenias, mostly thrombocytopenia (between 60 and 80∗109/L). The only significant complaint was intermittent tiredness. The common causes for thrombocytopenia in this setting were excluded—no evidence of graft versus host disease, no signs of viral or bacterial infection, and no signs of relapsed disease/dysplastic changes. The bone marrow smear performed 12 months after transplantation revealed an unsuspected diagnosis: a massive bone marrow infiltration with amastigotes.